How the COVID-19 pandemic is focusing attention on loneliness and social isolation - Smith, Ben; Lim, Michelle (Public Health Research & Practice, 2020)
The effects of the coronavirus disease 2019 (COVID-19) pandemic upon human health, economic activity and social engagement have been swift and far reaching. Emerging evidence shows that the pandemic has had dramatic mental health impacts, bringing about increased anxiety and greater social isolation due to the physical distancing policies introduced to control the disease. In this context, it is possible to more deeply appreciate the health consequences of loneliness and social isolation, which researchers have argued are enduring experiences for many people and under-recognised contributors to public health. In this paper, we examine the social and psychological consequences of the COVID-19 pandemic, with a focus on what this has revealed about the need to better understand and respond to social isolation and loneliness as public health priorities. Social isolation and loneliness are understood to be distinct conditions, yet each has been found to predict premature mortality, depression, cardiovascular disease and cognitive decline. Estimates of the prevalence and distribution of social isolation and loneliness vary, possibly ranging from one-in-six to one-in-four people, and the lack of knowledge about the extent of these conditions indicates the need for population monitoring using standardised methods and validated measures. Reviews of the evidence relating to social isolation and loneliness interventions have found that befriending schemes, individual and group therapies, various shared activity programs, social prescription by healthcare providers, and diverse strategies using information and communication technologies have been tried. There remains uncertainty about what is effective for different population groups, particularly for prevention and for addressing the more complex condition of loneliness. In Australia, a national coalition – Ending Loneliness Together – has been established to bring together researchers and service providers to facilitate evidence gathering and the mobilisation of knowledge into practice. Research–practice partnerships and cross-disciplinary collaborations of this sort are essential for overcoming the public health problems of loneliness and social isolation that have pre-existed and will endure beyond the COVID-19 pandemic.